Nutritional role of the natural productivity and formulated feed in semi-intensive shrimp farming as indicated by natural stable isotopes - Gamboa Delgado, Julián (Wiley, 2014)
The natural productivity of semi-intensively managed shrimp ponds is frequently represented by a high variety of trophic elements that continuously supply nutrients to the farmed organisms. As in the natural ecosystems, these dietary components exhibit differing isotopic signatures at natural abundance levels and since these natural communities belong to different trophic positions and isotopic values of organisms tend to increase with trophic level, the isotopic differences can be measured and used to infer on the transfer of nutrients, hence allowing establishing relationships between consuming organisms and their diets. Isotopic values can be measured and integrated in mass-balance mixing models in order to quantify the relative contribution of multiple nutritional sources to the growth of a specific organism. By applying such methodology, it has been possible to estimate the relative dietary contribution of several elements that belong either to the biota of the farming environment or that are part of formulated diets. Careful sampling methods and the isotopic analysis of these samples provide valuable information not only in terms of what the consumer organism has selected, captured and ingested, but also in terms of the proportions of assimilated nutrients in the consumers’ tissues. The present review highlights the nutritional relevance that the natural productivity of semi-intensively managed ponds and the supplied formulated feed represent for farmed shrimp. A synthesis of results from studies applying isotopic techniques to determine the relative contribution of dietary carbon and nitrogen derived from different biota elements and formulated feeds to the growth of shrimp is presented.